Answer:
(2,4)
Step-by-step explanation:
because the coordinates change places and signs
Answer:
Step-wwwkwnwby-step explanation:
Answer:
The answer for a different question is 5x
Step-by-step explanation:
DONT CHOOSE THIS. youll get wrong
Answer:
y = (x+3)^2 -1
Step-by-step explanation:
The vertex form of the equation is
y = a(x-h)^2 +k where (h,k) is the vertex
The vertex is (-3,-1)
y = a(x- -3)^2 -1
y = a(x+3)^2 -1
Pick another point (-2,0) and substitute it into the equation
0 = a(-2+3)^2 -1 to find a
0 =a(1)^2 -1
0 = a-1
1 = a
y = (x+3)^2 -1
Hi the picture has the answer and work, if you have any questions feel free to ask!!